Aptamer-Mediated Codelivery of Doxorubicin and NF-κB Decoy Enhances Chemosensitivity of Pancreatic Tumor Cells - David Porciani; Lorena Tedeschi; Laura Marchetti; Lorenzo Citti; Vincenzo Piazza; Fabio Beltram; Giovanni Signore (Elsevier, 2015)
Aptamers able to bind efficiently cell-surface receptors differentially expressed in tumor and in healthy cells are emerging as powerful tools to perform targeted anticancer therapy. Here, we present a novel oligonucleotide chimera, composed by an RNA aptamer and a DNA decoy. Our assembly is able to (i) target tumor cells via an antitransferrin receptor RNA aptamer and (ii) perform selective codelivery of a chemotherapeutic drug (Doxorubicin) and of an inhibitor of a cell-survival factor, the nuclear factor κB decoy oligonucleotide. Both payloads are released under conditions found in endolysosomal compartments (low pH and reductive environment). Targeting and cytotoxicity of the oligonucleotidic chimera were assessed by confocal microscopy, cell viability, and Western blot analysis. These data indicated that the nuclear factor κB decoy does inhibit nuclear factor κB activity and ultimately leads to an increased therapeutic efficacy of Doxorubicin selectively in tumor cells.